2021
DOI: 10.3390/app11041520
|View full text |Cite
|
Sign up to set email alerts
|

Moment Resisting Connection with Curved Endplates: Behaviour Study

Abstract: This article provides a behaviour analysis of moment resisting joints with curved endplates. This is a new type of connection that can be used for joining steel beams to the circular hollow section (CHS) columns by means of bolts. Some researchers apply the Eurocode model without considering the differences in calculation schemes and assumptions, such as by using the general model of an equivalent T-stub in tension. Consequently, many of the existing behaviour studies are somewhat misleading, thus there is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
2
Order By: Relevance
“…If the bolt forces can be directly measured by strain gages, the tension force acting on the T-stub component depends on the lever arm of internal forces z, which adds an additional layer of discrepancy. In previous study (Mudrov et al, 2021), the finite element analysis was implemented to determine the size of a lever arm. It was found that lever arm depends on the initial imperfections and that it is not constant, as the centre of compression tends to move outwards due to rotation of the joint.…”
Section: Verification Of Design Equationsmentioning
confidence: 99%
“…If the bolt forces can be directly measured by strain gages, the tension force acting on the T-stub component depends on the lever arm of internal forces z, which adds an additional layer of discrepancy. In previous study (Mudrov et al, 2021), the finite element analysis was implemented to determine the size of a lever arm. It was found that lever arm depends on the initial imperfections and that it is not constant, as the centre of compression tends to move outwards due to rotation of the joint.…”
Section: Verification Of Design Equationsmentioning
confidence: 99%
“…Disertacijos tema yra publikuoti 7 moksliniai straipsniai: trys -referuojamuose Clarivate Analytics Web of Science duomenų bazės leidiniuose, turinčiuose citavimo rodiklį (Mudrov et al, 2021a(Mudrov et al, , 2021b; vienaskonferencijų rinkiniuose, referuojamuose Clarivate Analytics Web of Science duomenų bazėje (Mudrov et al, 2019a); du -kitų tarptautinių duomenų bazių leidiniuose (Mudrov et al, 2019a(Mudrov et al, , 2022, vienas -konferencijų medžiagose (Mudrov, 2019c…”
Section: Darbo Rezultatų Aprobavimasunclassified
“…Nustatyta, kad jėgų pasiskirstymas lenktų tėjinių elementų varžtuose priklauso nuo tėjinio elemento ir varžtų standžių. Skyriaus tematika paskelbti keturi autoriaus straipsniai (Mudrov et al, 2021a(Mudrov et al, , 2021b(Mudrov et al, , 2019c.…”
Section: Tėjinio Elemento Su Lenkta Galine Plokštele Analitinis Model...unclassified
See 1 more Smart Citation